(untitled) (Biological Sciences - PJSIR, 2003)
Three species of rapeseed viz RM-9-7 (Brassica napus), BM-1 (Brassica juncea) and peela raya (Brassica carinata) were grown using normal agronomic practices. The leaves of three species were harvested after 20,40,60,80,100 and 120 days of sowing for analysis of different polyphenols after extraction in water and methanol by spectrophotometric methods. The results revealed that maximum concentration of sinapine, total phenols, leucoanthocyanidine and procyanidine were highest after 80 days of sowing in all species except the leucoanthocyanidine content of BM-I and peela raya species where maximum concentration was recorded after 100 days of sowing. Concentrations of methanol extractable phenolics were higher than water extractable phenolics in all species. Maximum values for methanol soluble sinapine (0.243%), total phenols (0.203%), leucoanthocyanidine (0.812 ? A 550/g) and procyanidine (? A 550/g) were found in RM-9-7, BM-1 and peela raya, respectively. It may be concluded that for optimum phenolics concentration in the extract, the leaves of these species should be harvested after 80 days.